A survey of content placement strategies for content-centric networking - Naeem, Muhammad Ali; Awang Nor, Shahrudin (IP Publishing LLC, 2016)
Current Internet design is not sufficient to encounter the huge Internet traffic, so it is converted from the host based on content in formation based architecture.Some of new content, information based architectures are PSRIP, CCN, NetInf, and DONA. In these ICN architectures, CCN is more attractive to implement the idea of Information Centric Network. And in network cache is most important part of all ICN architectures to implement the main idea of ICN. Ubiquitous cache is not a proof of good performance of the cache.To produce a high performance of cache there is needed to manage a cache in a more efficient manner.There exist many content placement strategies to manage the cache. In this paper, we briefly explain cache and content placement strategies of Content Centric Network architecture.